Morphologic changes of lung tissue in condition of consuming salts of heavy metals - Volkohon A.D. (Морфологія, 2009)
The work presents the results of research of a pulmonary tissue of 72 laboratory rats of different ages which within three months have been drinking water with salts of lead, chrome and zinc. By means of anatomical, histological, ultramicroscopic and spectrochemical methods it was established: a concentration of said before ions at the end of experiment was the most increased in lungs of young aged rats – on 126,85%, 104,28% and 34,44% respectively; the most significant morphological changes was noted in lungs of aged experimental rats: it was observed a signs of emphysema transformation (increasing of width of alveolus on 96,0%, width of entrance to alveolus - on 96,0%, width of conducting department - on 7,6%, decreasing of alveolar depth on 16,93%) and the signs of pneumosclerosis (accumulation of connective tissue in lungs and increasing of interstitial space on 11,34%). Noted changes were the result of toxic influence of combination of heavy metal salts on alveolar structures of lungs. This fact affects badly on respiratory function.